Answer:
Step-by-step explanation:
Simplifying
2x(3 + 4a) = -16x + 6x
(3 * 2x + 4a * 2x) = -16x + 6x
Reorder the terms:
(8ax + 6x) = -16x + 6x
(8ax + 6x) = -16x + 6x
Combine like terms: -16x + 6x = -10x
8ax + 6x = -10x
Solving
8ax + 6x = -10x
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-6x' to each side of the equation.
8ax + 6x + -6x = -10x + -6x
Combine like terms: 6x + -6x = 0
8ax + 0 = -10x + -6x
8ax = -10x + -6x
Combine like terms: -10x + -6x = -16x
8ax = -16x
Divide each side by '8x'.
a = -2
Simplifying
a = -2 <— answer